Musculoskeletal disorders among dental practitioners in Kulliyyah of Dentistry, IIUM Kuantan - Abdullah, Fatin Amirah; Norazam, Nurun Nadihah; Ahmad, Norhidayah; Ahmad, Norfaezah (UPM Press, 2024)
Introduction: It is common for dental practitioners to encounter stress, repetitive movements, and prolonged static postures that lead to musculoskeletal disorders (MSD). As a multifactorial disorder, MSD results in discomfort or pain in the affected body area. The MSD can adversely affect one’s job performance if the symptoms are left untreated. Hence, this study examined the risk factors, prevalence, and impacts of MSD on dental practitioners from Kulliyyah of Dentistry (KOD), International Islamic University Malaysia (IIUM) Kuantan. Materials and methods: By adopting the cross-sectional approach, this study assessed the risk factors, prevalence, and impacts of MSD on the study pop- ulation by using the modified validated Standardised Nordic Questionnaire (SNQ). The questionnaire was dissemi- nated to the study population via online Google Forms. The study population comprised of dental practitioners from KOD IIUM with more than one-year clinical experience. The survey outcomes were analysed via Chi-Square anal- ysis. Results: In total, 45 dental practitioners were involved in this study and the response rate was 83%. The results revealed that 86.7% of the participants suffered from MSD in at least one part of their body. Most of them had MSD in their neck region (62.2%), shoulder area (53.3%), and lower back part (48.9%). The common risk factors related to MSD were short breaks, prolonged static posture, and awkward posture. As MSD affected their work capacity, the participants suffered from stress and required medication prescriptions. Conclusion: The outcomes support the escalating evidence of the high prevalence of developing MSD among dental practitioners. Effective interventions and ergonomic awareness education should be implemented to minimise the incidence of MSD among dental prac- titioners to ensure optimum work performance.